Identifikasi Fungi Mikoriza Arbuskular Secara Mikroskopis pada Rhizosfer Tanaman Alang-Alang (Imperata Cylindrica L.) di Desa Sanur Kaja - ROMAULI THERESIA NAINGGOLAN; I GEDE PUTU WIRAWAN; I GEDE KETUT SUSRAMA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2014)
ABSTRACT Identification of Mikoriza Arbuskular Fungi in Microscopic the Rhizosphere of Reed (Imperatacylindric L.) in Sanur Kaja Village.   Mycorrhiza is a form of symbiosis between the fungus with a high level of plant (vascular plants, Tracheophyta), especially on the rooting. There is also a fungus with the other symbiotes, but the term mycorrhiza are typically for symbiotic plant roots which infect by fungus. This research aims to know the diversity of the genus or species of  mycorrhiza fungi arbuskular on the rhizosfer plant reeds in the village of Sanur Kaja, and to know whether or not there was colonization of mycorrhiza fungi arbuskular on the net root crops the reeds in the village of Sanur Kaja. The results of this research show that the symbiotes spores in the rhizosfer plant reeds is the genus Glomus multicaule spores, Glomus ambisporum, Acaulospora foveata, Gigaspora gigantae. Analysis on the plant roots mycorrhiza colonization reed showed a spherical structure called vesikular, while arbuskular is a structure on the hypha branches that resemble haustorium. (forming the pattern dikotom).   Key words: Acaulospora sp, Gigaspora sp, Glomus sp.